Pelatihan Pengolahan Limbah Tutup Botol Plastik dan Sosialisasi Digital Marketing di UKM Craft Pati - Mukhamad Nurkamid; Anastasya Latubessy (Muria Jurnal Layanan Masyarakat, 2022)
There are not many Usaha Mikro Kecil dan Menengah (UMKM) in Pati are utilizing the marketplace and digital promotion media to marketing their products. Based on the survey, 56% reasoned that they lacked understanding of digital promotional media, 42% said they did not have time to create content for digital marketing and 2% had difficult to access the Internet. Therefore through current service activities, providing skills to UKM Craft Pati through making accessories by utilizing plastic waste (mineral water bottle caps). The sales system uses digital marketing trends as a medium for promoting UKM products. Digital marketing is chosen as a means of promotion and sales because consumers can search for more products on the internet to find the best offers from all sellers compared to traditional methods. This activity get positive response from UMKM actors in Pati with an acceptance rate of UMKM as big as 86.15%.